Applied spatial statistics for public health data - Waller, Lance A., 1965- (Wiley series in probability and statistics., 2004)
An application-based introduction to the statistical analysis of spatially referenced health dataSparked by the growing interest in statistical methods for the analysis of spatially referenced data in the field of public health, Applied Spatial Statistics for Public Health Data fills the need for an introductory, application-oriented text on this timely subject.